Frequency of Epstein Barr virus infection among Sudanese children patients with Burkitt’s lymphoma - Muddathir, Abdel Rahim Mahmoud; Elradi, Wala Eldin Osman; Yousif, Badreldin; Abd allah, Elharam Ibrahim (International Journal of Advances in Medicine, 2020)
Background: Burkitt’s lymphoma (BL) is a B-cell malignancy categorized in three forms endemic, sporadic, and immunodeficiency-associated variants. Epstein barr virus (EBV) is associated with BL in almost all African populations. The frequency of EBV associated with BL is unknown in Sudan. The study aimed to estimate the frequency of EBV in Sudanese patients with BL. Methods: The study was a descriptive cross-sectional study conducted between June 2014 and July 2019 in 34 paraffin-embedded tissue sections obtained from diagnosed BL patients attending Soba university hospital in Khartoum city (Sudan). Monoclonal IgG1 antibody was used to detect EPV by immunohistochemistry technique. Results: The study showed that 44.1% (15/34) of BL patients were positive for EBV, whereas 55.9% (19/34) showed negative EBV. Males, 66.7% (10/15) were more affected by the EBV infection than females, 33.3% (5/15). P value=0.014. Conclusions: Despite BL is considered a rare type of lymphoma in Sudan; the obtained results showed a lower frequency of EBV compared with other studies worldwide.